ASSOCIATION OF NEUTROPHIL LYMPHOCYTE RATIO WITH SEVERITY AND OUTCOME OF ACUTE ISCHEMIC STROKE PATIENTS - Chande, Abhishek; Bawankule, Shilpa; Kumar, Sunil (International Journal of Psychosocial Rehabilitation, 2020)
The cumulative incidence of stroke ranged from 105 to 152/100,000 persons per year, and the crude prevalence of stroke ranged from 44.29 to 559/100,000 persons in different parts of the country during the past decade. Stroke is the second leading cause of death worldwide and mostly presents acutely. Among the strokes, ischemic stroke accounts for approximately 80% to 85% of the cases, and is characterized by the disruption of cerebral blood. Acute ischemic stroke is an inflammatory event where the ischemic tissues release chemokines and cytokines, and recruit peripheral circulating leukocytes. Among the leucocytes, neutrophils were found to be an important mediator and early neutrophilia was found to be associated with larger stroke volumes and poor prognosis lymphocytes also infiltrate the ischemic tissues and mediate inflammatory responses neutrophil- lymphocyte ratio as an inflammatory marker has been shown to be associated with poor prognosis in patients with malignancies and acute coronary syndrome.